Anxiety related to spoken English among UNITI students / Nur Afifah Rosli - Rosli, Nur Afifah (2013)
The issue of speaking anxiety has been widely discussed in Malaysia as it affects the future graduates' proficiency in speaking. A study was conducted in order to identify the level of anxiety in speaking English as a second language and the factors contribute to speaking anxiety among Diploma in Early Childhood Education in Kolej UNITI. This study also examined the relationship between the level of speaking anxiety noted by McCroskey (1970) and the three common factors that contribute to speaking anxiety as identified by Horwitz (1986) namely; communication apprehension (CA), test anxiety (TA) and fear of negative evaluation (NE). Furthermore, this study also identified other factors that could possibly contribute to speaking anxiety. The present study adopted a mixed method where data were obtained through questionnaire and semi-structured interview. The numbers of sample involved in this study were 200. The students were all 1st year students of the program. These students were selected from a pool of high to low achievers in Malaysia based on their SPM results. Findings of the study revealed that majority of the student's possessed high level of anxiety. The students' experienced enormous fear in term of articulating and understanding oneself which fall under communication apprehension compared to other two factors. It was found that the level of speaking anxiety and the three factors are not statically related. The data obtained from the semi-structured interview revealed that there are other factors namely; self-perception, teachers' role and deficiency in English language element such as vocabulary, grammar, etc. that contribute to speaking anxiety among the students. Hence, several implications and recommendations were outlined as to how speaking anxiety among the respondents may be overcome.